Tipologi Zaman Nuh dalam Lukas 17:26–27: Analisis Teologis atas Kedatangan Anak Manusia dalam Kajian Intertekstual Alkitabiah - Darmadi, Daud; Agustina , Eunike (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2025)
This study examines the eschatological typology of Noah’s era in Luke 17:26–27 as a theological framework for the coming of the Son of Man through a biblical intertextual approach. The central issue is how Luke utilizes the flood narrative (Genesis 6–7) as a typological paradigm to depict the sudden nature of Christ’s second coming. This qualitative research employs a literature-based study using G.K. Beale’s intertextual exegesis model, which consists of nine systematic steps for analyzing the relationship between Old and New Testament texts. Hermeneutical and exegetical approaches are applied to interpret theological meaning by tracing textual allusions and rhetorical structures. The findings reveal that Luke constructs the typology of Noah’s era not to emphasize explicit wickedness, but rather to critique a lifestyle preoccupied with worldly activities and lacking eschatological awareness. The generation in Noah’s time engaged in eating, drinking, and marrying serves as a reflection of the spiritual condition of the end-time generation that lives in spiritual indifference. The intertextual analysis demonstrates a strong use of Septuagintal allusions, with adapted narrative structures from Genesis 6–7 to affirm the certainty of eschatological judgment. The study concludes that the typology of Noah’s era functions as a prophetic-pastoral warning, urging believers to live in eschatological vigilance, with Noah portrayed as a typological figure of the righteous who perseveres in faith. The theological implication highlights the importance of eschatological ethics, which demands spiritual awareness and faith readiness in facing the sudden coming of the Son of Man.